Recent Advances of Solutions Algorithms for Logistics Routing Problems - Erfan Babaee Tirkolaee; Alireza Goli; Behnam Malmir (Logistics)
Nowadays, the business landscape is highly focused on establishing efficient logistics systems, with numerous companies striving to gain a strong foothold in the global market and achieve maximum productivity and cost effectiveness [...]